Comparative mapping of cross-reactivities of milk proteins from different goat breeds with cow's milk allergens by proteomic approach - Mansor, Muzammeer (2022)
Cow’s milk allergy is prevalent among atopic children and the exclusion of milk proteins from their diet is the most common solution in managing the allergic symptoms. Milk from other ruminants such as goats have previously been thought to be a good alternative to cow’s milk for cow’s milk protein allergic (CMPA) individual but there are increasing evidence of their proteins to have cross-reactivities to cow’s milk allergens. However, no conclusive studies have been done in comparing the allergenic potential between the different goats breed that cross-reacted to cow’s milk allergens. This study therefore aimed to profile and compare milk proteins from different goat breeds that have crossreactivities to cow’s milk allergens using proteomic approach. Two-dimensional gel electrophoresis (2DE) coupled with immunoblotting with allergen-specific serum IgE and mass spectrometry was applied to accurately identify and profile multiple allergens in protein samples. Efficacies of three protein extraction methods; a milk dilution method in urea/thiourea based buffer (Method A), a triphasic separation protocol in methanol/chloroform solution (Method B), and a dilution in sulphite-based buffer (Method C), were first evaluated for the 2DEproteomic on milk from two different goat breeds, Saanen and Jamnapari. Method A was selected as the most suitable method with 72.68% and 71.25% protein recovery, 199±16.1 and 267±10.6 total spots resolved on 2D gels, optimal spot resolution and minimal streaking for Saanen and Jamnapari samples. Protein profiles of skimmed milk extracts from Saanen, Jamnapari, and Toggenburg (n = 6 animals/ breed) were then compared by 1D- and 2D-gel electrophoresis (2DE). Cow’s milk was used as a control (n = 6). Proteins that cross-reacted with serum IgE of CMPA patients (n = 10) were compared and identified by IgE-immunoblotting and mass spectrometry. Matrix-assisted laser desorption ionisation time-of-flight tandem mass spectrometry (MALDITOF/ TOF MS) analysis of IgE-reactive proteins detected in the milk of the three goat breeds revealed that the protein spots identified with high confidence were proteins that are homologous to common cow’s milk allergens such as αS1-casein (αS1-CN) (spots 402, 1239, 1282, 385, 2664, 1263, 2667), β-casein (β- CN) (spot 1334), κ-casein (κ-CN) (spots 1438, 1392, 1388), and betalactoglobulin (β-LG) (spot 2661). Among the dairy goat breeds evaluated in this study, Jamnapari’s milk proteins were shown to have cross-reactivities with four main milk allergens; α S1-CN, β-CN, κ-CN, and β-LG. Saanen goat’s milk proteins, on the other hand, cross-reacted with two main milk allergens, α S1-CN and β-LG, while Toggenburg goat’s milk proteins exhibit reactivity to only one of the main milk allergens; κ-CN. Although milk from different goat breeds had similar protein composition, the variation in breed was observed to have affected the IgE- reactivity of the milk protein. The findings of this study may provide more information for future research on the hypoallergenic potential of milk from different breeds or species, as well as the effect of genetic variation on the composition and structure of protein on cellular activities.